2021
DOI: 10.1016/j.celrep.2021.108984
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of a common solution for broad ebolavirus neutralization by glycan cap-directed human antibodies

Abstract: Highlights d Glycan cap antibody-mediated GP destabilization correlates with synergy d Cryo-EM structures reveal antibodies target a highly conserved epitope d Antibodies use long CDRH3 loops to displace and mimic portions of the glycan cap d Glycan cap antibodies block cleavage events required for viral entry

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 85 publications
1
33
0
Order By: Relevance
“…In summary, our data support and expand existing data sets about the importance of antibodies directed to the EBOV GP GC for protection from EVD [31,32,38]. Our findings also demonstrate that both the GC and MLD are dispensable for VSV-EBOV-based vaccine vector replication in vitro .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In summary, our data support and expand existing data sets about the importance of antibodies directed to the EBOV GP GC for protection from EVD [31,32,38]. Our findings also demonstrate that both the GC and MLD are dispensable for VSV-EBOV-based vaccine vector replication in vitro .…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the monoclonal antibody cocktail ZMapp contains the GC-binding antibody 13c6 [37]. Recently, inhibition of cathepsin cleavage by these GC-binding antibodies was proposed as a mechanism [38]. Therefore, while a deletion of the GC and MLD might not interfere with the GP’s ability to drive VSV replication, it could result in reduced protective immunity against EBOV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies showed that memory B cells in several individuals used genetically similar B cell receptor genes to encode neutralizing mAbs (20,56,57). Another study described common structural and genetic features of the glycan cap recognition by several broadly-reactive human mAbs isolated from memory B cells (41). In our study of serological response in one donor we characterized three major epitope classes of mAbs using a relatively small panel of 52 mAbs.…”
Section: Discussionmentioning
confidence: 96%
“…For individual mAbs, alanine scanning mutagenesis studies identified key binding site residues that mostly were located on the top part of the glycan cap (Figures 4, 5B). Many of these residues were defined previously by us and others as key contact residues for potent neutralizing glycan cap-specific human mAbs BDBV-289 (W275), EBOV-237 (N278), EBOV-337 (W275), EBOV-442 (W275, P273), and EBOV-548 (T240, T270, I274, W275), weakly neutralizing protective murine mAb 1H3 (K276), or the non-neutralizing protective mAb 13C6 (T270, K272) (6,33,40,41). We also assessed mAbs from this study in a competition-binding assay and demonstrated competition with mAb 13C6 for GP binding, which confirmed the glycan cap specificity of these mAbs (Figure 4).…”
Section: Major Antigenic Binding Sites Targeted By Class-representative Plasma Mabs Revealed Common Featuresmentioning
confidence: 99%
“…It binds to its epitope with 5× greater affinity once EBOV-548 is bound to the GC. Together, EBOV-520 and EBOV-548 can fully protect NHPs from mortality, though EBOV-520 alone has also demonstrated partial protection in animal models [ 82 , 83 , 84 ]. Finally, 13C6 is a non-neutralising antibody from the ZMapp cocktail that binds to the GC but is removed during cathepsin cleavage.…”
Section: Antibody-based Therapeutics and Vaccinesmentioning
confidence: 99%